Radiation protection of itinerant workers. (Safety reports series ;, 2015)
"This publication addresses the protection and safety issues associated with the use of itinerant workers. Such workers are defined for this report as occupationally exposed workers, who work in supervised and/or controlled areas at one or more locations and are not employees of the management of the facility where they are working. It focuses on the necessary communication and cooperation to establish a clear allocation of responsibilities among the relevant parties, including the itinerant worker, the employer of that worker and the management of the facility at which the work is occurring. Managerial and practical arrangements are described, to ensure the protection and safety of itinerant workers. Discussion topics include dose tracking and control, training, safety culture development and application of the requirements for protection and safety coherently with other requirements."--Publisher's description.